Computer-aided dental comparison for mass disaster identification - Ibanez, Oscar; Ramirez, Guillermo; David Villegas, Antonio; Kahana, Tzipi (Національний науковий центр «Інститут судових експертиз ім. Засл. проф. М.С. Бокаріуса», 2023)
PhD in Forensic Anthropology, Associate professor, The Hebrew University of Jerusalem, Israel, La Coruna, Spain, e-mail: kahana.tzipi@gmail.com In this work we develop an accurate algorithm to compare and match AM and PM dental records calculating a score based on different codification systems.
Keywords: forensic odontology; human identification; dental comparison; odontograms; disaster identification; artificial intelligence